An 'alcohol contract' has no significant effect on return to drinking after liver transplantation for alcoholic liver disease. (15th March 2014) - Masson, Steven; Marrow, Benjamin; Kendrick, Stuart; Elsharkawy, Ahmed M.; Latimer, Sandra; Hudson, Mark
Summary Return to drinking after liver transplantation for alcoholic liver disease (ALD) remains a source of unease with varying reported rates of return to drinking and impact this has on graft function. In 2005, the UK Transplant liver advisory group recommended an 'alcohol contract' in which ALD patients listed for transplantation confirmed in writing their commitment to abstinence. We aimed to measure the rates and consequences of return to drinking alcohol in a UK transplant programme and assess the effect of the 'alcohol contract'. Consecutive patients transplanted for ALD during 1996–2011 were included. Every patient listed after Feb 2007 signed up to the 'alcohol contract'. We compared rates and pattern of return to drinking and survival before and after the introduction of the contract. Overall, 52 (37%) patients returned to drinking alcohol; 37 (39%) before and 15 (34%) after the contract. There was no significant difference in the rate of return or pattern of drinking. Median survival was 176 months (145–207 95% CI). There was no significant difference in survival, mortality rates, or in the causes of death in either group. We report high rates of return to drinking alcohol in a UK liver transplant programme. Despite this, the impact on patient and graft survival is low. There is no evidence that an 'alcohol contract' has had any effect on alcohol consumption.